Students’ Mathematical Literacy Ability: Evaluation of Validity and Reliability - Salam, Asa Raila; Fikriyati, Adzkia; Faradillah, Ayu; Miyatun, Asih; Salam, Abd (Pattimura University, 2024)
Mathematical literacy is the ability to understand, use and convey mathematical concepts in various contexts known as mathematical literacy. In Indonesia, the level of students’ mathematical. Mathematical literacy is the ability to understand, use, and convey mathematical concepts in various contexts known as mathematical literacy. In Indonesia, the level of students' mathematical literacy skills is still low. This research aims to evaluate the validity and reliability of mathematical literacy test instruments using Rasch Model and SPSS. This research used a quantitative method with a survey approach involving 100 high school students from various demographic backgrounds, the instrument must be valid and reliable to ensure accurate measurement. The results of the analysis showed that the instruments tested has the same result which is invalid on item 5 and have good reliability of 0.639.